Penegasan Kembali Pendekatan Sukarela dalam Kerangka Bisnis dan Hak Asasi Manusia di Indonesia: Akuntabilitas Korporasi dan Kerusakan Lingkungan - Heribertus Jaka Triyana; Chandrika Kumaratungga (Jurnal HAM, 2026)
This article aims to evaluate the existence and relevance of the voluntary principle for the better protection of human rights and business in Indonesia, where multinational and transnational corporations have allegedly been violating human rights. The analysis in this paper is mainly construed by normative assessment of the existence of the voluntary principle for business and human rights as bridging gaps on human rights duty bearers between States and non-state actors, i.e., multinational and transnational corporations in Indonesia, in terms of its area, scope, and institutionalization. This article reveals that the voluntary principle has been deemed internal-driven motivation and authority, and that the best approach is to allocate all available resources to effective branding and positive stereotyping in Indonesia to minimize public scrutiny of human rights violations. As a result, the voluntary principle, used as the basic principle for the operations of multinational and transnational corporations, provides only a good image rather than a binding instrument to which future advocacy is directed to halt future human rights violations. It is time to stipulate this principle-binding rule for human rights due diligence and to conduct audits for corporations.